The mediating role of new ecological paradigm between value orientations and pro-environmental personal norm in the agricultural context. Issue 2 (11th April 2016) - Chua, Kean Boon; Quoquab, Farzana; Mohammad, Jihad; Basiruddin, Rohaida
Abstract : Purpose: – Environmental awareness became a crucial agenda for both academicians and practitioners. Effect of the individual's value, belief and norm on their environmentally significant behaviour is vital on subsequent purchase decision of the consumers. Considering this, the purpose of this paper is to examine the relationships among value orientations, new ecological paradigm (NEP) and pro-environmental personal norm (PPN). Moreover, this research intends to investigate the mediating role of NEP between value orientations and PPN. Design/methodology/approach: – This study has utilized questionnaire survey among 277 paddy farmers at the Muda Agricultural Development Authority area in Malaysia. Data were analysed using partial least squares technique in order to test study hypotheses. Partial least square technique was utilized to analyse the data to test the study hypotheses. Findings: – Results reveal that biospheric value, altruistic value and egoistic value positively and significantly affect NEP. It is also found that NEP positively and significantly affect PPN. Data also supports the links between altruistic value and PPN. However, the relationship between other two value orientations (biospheric value and egoistic value) and PPN is not supported by the data. Additionally, NEP mediates the relationship between biospheric value and PPN as well as between egoistic value and PPN. Contrary to this, NEP does not mediate the relationship between altruistic value and PPN. Practical implications: – The findings of this study will guide the agrochemical industry to understand how to enhance consumers' behavioural aspect towards the environmental welfare. As handling of agrochemical is hazardous to health and environment, the knowledge on the effect of value orientation, belief and norm holds the key to inculcate good agricultural practice. Originality/value: – The present study is among the pioneers to consider NEP as the mediator between three types of value orientation and personal norm. Additionally, this study examined the relationship between NEP and PPN as well as between value orientations and PPN which are comparatively new to the existing body of literature. Nevertheless, this study considers NEP as a multidimensional constructs which is relatively new. Last, but not the least, the findings elaborate the existing knowledge of individual's environmental concern in the context of agrochemical purchase.